2020
DOI: 10.12688/aasopenres.13028.1
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of bioremediation-cocktail for application in the eco-recovery of crude oil polluted soil

Abstract: Background: Environmental sustainability is the driver for finding the optimal bioremediation cocktail with the combination of highly potent hydrocarbonoclastic strains and the nutrient additives that significantly enhance mineralization of crude oil in polluted soil in order to mitigate its deleterious effects on the environment. In this study, four hydrocarbon-degrading bacterial strains were pre-selected from mined rhizobacterial isolates in aged crude oil-contaminated soil.  Method: Agrowaste residues of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Monoculture cultivation and fermentation have limits. Other research has identified the role of mixed cultures in mitigating the issues that monoculture systems face [31,32,25,33].The congruency of model parameters obtained in this study is likewise consistent with a trend previously described by other researchers. The substrate consumption rates (14.28 and 11.16 mg/g/day) for the cassava whey and yeast extract with an R 2 value of 0.96 an d 0.94 respectively indicated that there was a healthy utilization of Cassava whey and yeast extract for the generation of oxalic acid and that the process was growth associated.…”
Section: Resultssupporting
confidence: 91%
“…Monoculture cultivation and fermentation have limits. Other research has identified the role of mixed cultures in mitigating the issues that monoculture systems face [31,32,25,33].The congruency of model parameters obtained in this study is likewise consistent with a trend previously described by other researchers. The substrate consumption rates (14.28 and 11.16 mg/g/day) for the cassava whey and yeast extract with an R 2 value of 0.96 an d 0.94 respectively indicated that there was a healthy utilization of Cassava whey and yeast extract for the generation of oxalic acid and that the process was growth associated.…”
Section: Resultssupporting
confidence: 91%
“…The main pathogens that were found in the present population were represented by 13 strains: Serratia surfactantfaciens (10%), Staphylococcus epidermidis (5%), S. pasteuri (65%), Stenotrophomonas maltophilia (5%), Pseudomonas aeruginosa (10%), Delftia tsuruhatensis (5%), Acinetobacter calcoaceticus (5%), Granulicatella adiacens (5%), Raoultella planticola (10%), R. ornithinolytica (5%), A. agilis (35%), Pseudomonas stutzeri (5%), and Acinetobacter junii (5%). Sources of contamination are normally residential water, rivers, soil, mud, and some plants [ 19 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], which might be related to the CL care routines and nonhygenic environments. For contamination by nonpathogenic species, 13 strains were found: Brevundimonas albigilva , E. mori, Herbasprillum aquaticum, Kluyvera intermedia , Pseudomonas geniculata , Acinetobacter lactucae , Bacillus wiedmanni , Curtobacterium plantarum , Paludibacterium paludis, Kosakonia oryziphila , Rothia kristinae , Acinetobacter soli, and Streptococcus periodonticum.…”
Section: Resultsmentioning
confidence: 99%
“…(2020) [ 36 ] Agbaji et al. (2020) [ 37 ] Vandamme et al. (2016) [ 38 ] P. stutzeri 5 soil, water Gilardi (1972) [ 39 ]; Lalucat et al.…”
Section: Resultsmentioning
confidence: 99%
“…Permeability of the soil using the samples was determined through the ASTM-D2434 method while Atterberg Limits was determined using ASTM-6913 for a soil moisture test. The pH of the soil samples was determined using the electrochemical method Agbaji et al, [22]. Electrical conductivity was determined using the method of APHA, [23].…”
Section: Geotechnical and Physicochemical Evaluation Of Pome-impacted Soilmentioning
confidence: 99%
“…The exchangeable ammonia or ammoniacal nitrogen was determined using the APHA, [23] method. The modified methods of Effiong et al [24]; Orhohoro et al [25] and Agbaji et al, [22] was employed in the analysis of parameters such as heavy metals, hydrogen sulphides and salinity.…”
Section: Geotechnical and Physicochemical Evaluation Of Pome-impacted Soilmentioning
confidence: 99%